Faktor-Faktor Penentu Rekrutmen Perusahaan di Industri Teknologi, Servis, dan Konsultasi - Givari Rizky; Anindia Gita Karlinda; Indrawan Adi Sucipto; Nindya Ayu Widyanugrah (Indonesian Business Review, 2022)
The purpose of this paper is to dig deeper into what is actually assessed by the talent acquisition process in finding the workforce that the company needs. The methodology that the author uses is mixed-method research, which is a combination of qualitative research and quantitative research. Quantitative research was carried out by distributing questions to 150 respondents of HR employees in Jakarta with > 2 years of experience, who worked in the technology, service, and/or consulting industry, who were members of the FTHR group. The implementation of quantitative and qualitative research on HR practitioner respondents who work in various industries and have long experience in their fields, has given the author a new understanding that was previously poorly understood. The results of this research help to create a clearer picture of the opportunities that can be created through recruitment problems, as well as inconsistent recruitment results that can lead to continuing problems.